Welfare Impacts and Transaction Costs of Fisheries Co-Management at the Oxbow Lakes (BAORS) in Bangladesh - E-Jahan, Khondker Murshed (2000)
Fisheries co-management starts with the premise that stakeholders have the innate capacity to improve resource conditions as well as the welfare of the society. Recent investigations have shown that the co-management approach for governing natural resources can result in higher levels of productivity, and lower administration and enforcement costs than the national and centralized management approach. This suggests a need for rapid and substantial evaluation of fisheries management institutions. The main purpose of this study was to examine the economic performance of the fisheries co-management institution in the Oxbow Lake fisheries of Bangladesh. Firstly, this study examined net welfare change to society as a result of the introduction of a co-management system. Secondly. the resource rent and transaction costs analyses were used to evaluate the efficiency of the co-managed institution compared to the centralized management institution. The simultaneous equation model consisting of supply, demand and identity equations were estimated and Marshallian surplus measurement was used to estimate the welfare change with and without the co-management system. A cross-sectional heteroskedastic and time wise autoregressive model proposed by Kmenta (1986) was utilized for the estimation. The analysis showed that the co-management program had caused a welfare gain to society amounting to 1805186 Tk (USD 38989) from the original situation. Both consumers and producers gained by the project intervention, however, consumer welfare gain was bigger valued at 1762399 Tk (USD 38065) than that of producers valued at 42787 Tk (USD 924). The Oxbow Lake co-management system had also resulted in higher rent of 19802 Tk/ha (USD 427 per ha), compared to the rent in government managed Lakes of 5652 Tk/ha (USD 122 per ha). The results also showed that return to capital and labor was also high in most of the co-managed Lakes compared to the government-managed Lakes. Static and dynamic processes were utilized in this study to measure the transaction costs of fisheries management. The results presented in this thesis showed that transaction costs of managing the fisheries were lower under a c0- management arrangement i.e. 2938 Tk/ha (USD 63 per ha) than the centralized management system of 4707 Tk/ha (USD 102 per ha). The results from the analysis showed a better performance for the co-managed Lakes compared to the government-managed Lakes. The findings revealed that the lower transaction costs and higher resource rents are the result of the increased legitimacy inherent in the co-management system. This increased legitimacy encouraged fishers to develop cooperative approaches for effective management of the Oxbow Lakes.